Effect of Multilateral Trade Liberalization on Services Export Diversification - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2021)
The present study is an extension of the work on the effect of multilateral trade liberalization (MTL) on export product diversification undertaken by Gnangnon (2019b). The analysis focuses on the effect of MTL on services export diversification. The analysis has revealed that MTL is associated with greater services export diversification in both developed and developing countries alike. This is particularly the case in countries with a high reliance on manufactured goods exports or those that enjoy greater export product diversification. Interestingly, MTL enhances services export diversification in countries that experience higher foreign direct investment inflows. Overall, through its positive effect on both export product diversification and services export diversification, greater cooperation among World Trade Organization (WTO) Members on trade matters could help revive economic growth, particularly in the current COVID-19 pandemic that has significantly plummeted it.
Keywords: O14; F13; F14; 330; Multilateral trade liberalization; Services export diversification; Export product diversification; Foreign direct investment inflows